An Inverse Approach to Estimate Heat Transfer Coefficients of 122 mm Medium-Range Missile During Correction Engine Operation - Janusz ZMYWACZYK; Piotr KONIORCZYK; Marek PREISKORN; Bogdan MACHOWSKI (Problemy Mechatroniki)
This paper presents an inverse approach to estimate the heat transfer coefficients on the inner and the outer sides of a cylindrical shield made of R35 steel containing a gas-dynamic control block of a 122 mm medium-range missile during the combustion of propulsion charge in a correction engine. The specific heat and the thermal diffusivity of R35 steel was experimentally determined using both Netzsch DSC 404F1 Pegasus and LFA 427 measuring devices, respectively. The obtained temperature characteristics of the thermo-physical parameters of cylindrical shield materials were then used to calculate the temperature field concerning the main problem. The inverse problem based on the parameter estimation method using Levenberg–Marquardt optimization procedure was applied to find the unknown heat transfer coefficients. To solve the inverse problem the temperature histories at some locations of the cylindrical shield were known from the experiment. For this purpose a test measuring stand was built and during the combustion process of the propulsion charge inside the cylindrical shield containing the correction engine the temperature distribution on the outer surface of the cylindrical shield was recorded by means of a high-speed infrared camera (PhantomV210). A two-dimensional axial-symmetric nonlinear heat conduction model which takes into account the heat loss due to convection and radiation was solved using the Finite Volume Method (FVM). It was found that the assumption of fixed heat transfer coefficients on both sides of the cylindrical shield was sufficient enough to achieve a satisfactory compliance between the measured and the calculated temperature histories at the same location.